Evaluation of dried Khat (Catha Edulis) leaf as natural additives on egg quality, embryonic mortality, and chick quality of white leghorn layers - A. G. Asfaw; M. G. Abebe; E. K. Senbeta (Diponegoro University, 2022)
An experiment was conducted to evaluate the effects of supplementation of Khat leave as a natural feed additive on egg quality, fertility, embryonic mortality, hatchability, and chick quality of White Leghorn (WL) layers. One hundred fifty-six hens and twenty-four cocks of WL at twenty-four weeks of age were randomly dis-tributed to four treatments, each replicated three times with thirteen layers and two cocks per replication and kept on a deep litter system. Treatment rations were formulated by the addition of Khat leave on layers ration with the proportion of 0% (T1), 0.2% (T2), 0.4% (T3), and 0.6% (T4). All data were subjected to analysis of variance. The egg weight of layers in T3 (54.1) was higher (P<0.05) than that of layers in T4 (51.5) and T1 (51.8). Roche color reading was significantly higher for T4 (4.7±0.19) than T3 (3.4±0.19), T2 (2.2±0.19), and T1 (1.7±0.19). There were no significant differences (P > 0.05) among treatments in yolk height, yolk index, yolk diameter, albumen height, Haugh unit, fertility, hatchability, chick weight, and visual score. Embryonic mortality percentage was significantly (P<0.05) higher for T1 than for other treatments. Chick length was significantly (p<0.05) higher in T2, T4, and T3 than in T1. Finally, this study can be concluded that the use of dried Khat leaves as an additive up to 0.6% in ration of White Leghorn layers increased eggshell weight and yolk coulor and reduced embryonic mortality.